The British electrical industry, 1875-1914 - Byatt, I; Byatt, I. C. R. (1962)
﻿ This is a study in the beginnings of an industry. The electrical industry was chosen for two reasons. Firstly its story is that of the beginnings of the substantial economic application of a new technology. Secondly it was an important industry in the British economy at the time. It has sometimes been argued that the slow growth of this industry is one of the reasons for the slow growth of the economy. Thus the material has been principally organised around two matters, innovation and technical progress, and the allegedly slow growth of this industry in Britain before 1914. The electrical industry has been widely defined. I have taken the three principal uses of electricity at the time, lighting, traction and (non traction) motor power, and looked at the introduction and early growth of electrical methods. Thus the industry is defined within technological bounderies. I have included electricity supply, electric traction and the manufacture of electrical machinery - all of which could be treated as separate industries. Thus I have dealt with heavy electrical engineering, and have ignored the light electrical engineering of the time, which was connected with the use of electricity for telegraphs and telephones. Electro chemistry has also been ignored as the scarcity of cheap water power in Britain made it unlikely that it would develop to any considerable extent in Britain. Roughly speaking, electric lighting, traction and power were new methods of providing existing products, light, rail transport (by train or tram) end factory turnover. Therefore in Chapters 1, 5 and 6 I have looked at the cost of the new electrical methods compared with existing methods, or more accurately have tried to see what resources would be saved by using electricity. However one cannot expect the only reason why new technical developments were (or were not) adopted, or adopted quickly or slowly to be that they did (or did not) have resources. Thus I have locked at other variables, like the rate of growth of the economy, the timing of cyclical fluctuations, legislation and relations between business and technology. Attempts have been made to illuminate the English experience by contrasting it with the situation in the United States. In Chapter 1 I have argued that the principal reason for the apparant failure of the attempt to establish electric lighting in this country in the early 1880s was the low price of gas. As the price of electricity relative to gas fell during the 1880s and 1890s electric lighting became more widely used. However it does not seem to have been until the introduction of the metal filament lamp in the years 1908-10 that electric lighting had the same advantage, relative to gas that it seems to have had in the United States as early as the middle 1880s. Also the slower rate of urbanisation in Britain compared with the United States, and the timing of the cycle affected the rate of adoption of electric lighting. Chapters 2 and 3 deal with the use of electric lighting when electricity was provided from a central station. In Chapter 5, Section I I have argued that electric trams saved resources, but that their adoption was delayed in the early and middle nineties by the effect of the Tramway Act, the unprofitability of horse trains, the lack of interest of home electrical manufacturers, the attitude of the municipalities and their relations with joint stock enterprise. I have argued that the boom in electric traction 1897-1903 was stimulated by the building cycle, the rising demand for transport, and the entry of American firms. After 1903 the boom died away as demand had been satisfied. Demand rose only slowly as tramways do not appear to have stimulated suburban building in the short run. In Section II I have discussed urban electric railways, particularly the London Underground. I have stressed the importance of American engineering and enterprise in promoting resource saving innovations. I have also argued, although the matter is complicated by questions of lay out and fares that the low profitability of urban electric railways showed that demand was limited. In Section III I have tried to show why the suburban lines of main line steam railways were only slowly electrified. I have argued that electric traction would have only been adopted had it been capital saving. Where tramway competition made capacity redundant, electrification was not worth while. In Chapter 6 I have examined factory electrification. My tentative conclusions are that while electric transmission of power was probably on balance fuel saving, its capital costs were greater than those of mechanical transmission before 1901-O5, although after that they were, on balance, as low. However the evidence suggests that substantial resource saving would only have accrued from electrification if it had taken place in conjunction with other changes in the techniques of production. However there are enormous difference between industries and an important reason for the apparently slow rate of factory electrification in England is that its advantages were perhaps least in two of the great power using industries, textiles and mining. In addition electricity supply and the manufacture of electrical machinery have been dealt with in some detail. Their combined influence on the cost of electrical methods was very great. Costs in these sectors fell regularly as the process of innovation continued. The prices of other inputs of electric lighting, power and traction generally fell less than those of the products of those two sectors. Also they held a central position in the process of innovation. Moat innovations were adopted on their initiative, and they were responsible for making adaptions to other machinery and to buildings. The electricity supply sector is dealt with in Chapters 2, 3, 4, 9 and 10. In Chapters 2 and 3 I have looked at the general development of electricity supply largely by discussing the major innovations and trying to see how their adoption might have reduced, or did reduce, costs. I have also tried to put the story of the beginnings of electricity supply on a sound statistical basis by constructing time series of investment in electricity supply and sales of electricity for lighting power and traction. Chapter 4 deals with the attempts substantially to increase the area of supply and shows how the only successful attempt involved come important innovations. Particular attention has been givcn to developments in electrical machinery. This is partly because the makers of electrical machinery have also been dealt with in detail. Chapters 9 and 10 are on the control of electrical utilities and their pricing policy. It has often been said that legislation delayod the development of the industry and Chapter 9 is an attempt to examine the inadequacies of the public utility control at the time. It ia shown both that it worked very crudely, and thzt it had a tendency to keep profits low by keeping costs high. In Chapter 10 it is shown that the usual pricing system of electricity supply undertakings was based on a theoretical misconception, and that it could lead to distortion of resources. The pricing policy of electric traction undertakings is shown to be perverse because of the attempt to help workmen to live in better houses. The makers of electrical machinery are considered in Chapters 7 end 8. Three important issues have been dealt with, the process of innovation, the question of new entry into this new industry, and the workings of competition. The three are intimately connected. Innovations in machinery often involved the entry of new firms. The workings of competition taken together with the nature of the cyclical fluctuations in the demand for electrical machinery, reacted on innovation. The speed of innovation affected the way competition worked. I have also discussed the effect which the British capital market had on the electrical manufacturers. Chapter 11 contains two sections. One is a summary of the process of innovation in the whole electrical industry. The other is a sketch of the financing of investment in electricity. I suggest that borrowing was only difficult in some sectors. The methods of calculating some of the Tables are in an Appendix. There is also a Technical appendix explaining some of the engineering matters.